2014
DOI: 10.4103/2211-4122.143961
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiovascular ultrasound in the evaluation of obese subjects

Abstract: Obesity represents a worldwide increasing health problem. Obesity, through complex and not fully understood pathogenetic mechanisms, induces different structural and functional changes of left heart chambers, right heart chambers, and arteries. Ultrasound techniques are the first choice for a comprehensive assessment of the cardiovascular adaptation to obesity. This review summarizes the up-to-date literature on the topic, with particular focus on the main clinical studies, which range over different cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…[ 29 33 ] Importantly, weight loss is capable of inducing cardiac reverse-remodeling. [ 3 34 ] Our data showed that WHtR had the highest AUC when we analyzed LA volume, LV diameter, LV volume, LVM and RWT, although the 95% confidence intervals were overlapping between the four studied indexes. wBMI had higher AUC than BMI for 2 out of 5 echocardiographic parameters of adverse cardiac geometry (LA volume and RWT), while WC had the lowest AUC for all 5 parameters.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[ 29 33 ] Importantly, weight loss is capable of inducing cardiac reverse-remodeling. [ 3 34 ] Our data showed that WHtR had the highest AUC when we analyzed LA volume, LV diameter, LV volume, LVM and RWT, although the 95% confidence intervals were overlapping between the four studied indexes. wBMI had higher AUC than BMI for 2 out of 5 echocardiographic parameters of adverse cardiac geometry (LA volume and RWT), while WC had the lowest AUC for all 5 parameters.…”
Section: Discussionmentioning
confidence: 79%
“…It was reported that parameters of central obesity (WC and WHtR) had a better correlation with aortic stiffness than BMI. [ 34 ] BSI is a marker for arterial stiffness, detecting subclinical atherosclerosis changes in the vessel wall, and it estimates the arterial compliance independent of the BP effect. [ 12 ] Our data showed that wBMI had the largest AUC in predicting increased BSI.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cardiac output, with little changes of heart rate, leads to LV remodeling. [3] Super obesity is associated with insulin resistance, with a worse impact on cardiac remodeling and LV diastolic function than morbid obesity. [1] Obese patients are 30% more likely to develop heart failure and each 1 kg/m 2 rise of BMI increases the risk of heart failure by 5% for men and by 7% for women.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and impaired blood glucose was defined according to revised American Diabetes Association criteria, as random blood sugar test. [3] The data collected was analyzed by SPSS Version 21.0 (IBM, Armonk, New York, United States) based program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation